Noigandres: from Provençal Troubadours to Brazilian Concretists - Cussen-Abud, F (UNIV CONCEPCION, FAC HUMANIDADES ARTE, 2024)
In this essay a network is traced between various poets from different eras and languages: the Proven & ccedil;al troubadour Arnaut Daniel, the Tuscan poet Dante Alighieri, the modernist Ezra Pound and the brothers Haroldo and Augusto de Campos, members of the Noigandres group and founders of the movement of Concrete poetry in Brazil. This network corresponds to a series of mentions, tributes and versions that respond to a common vision of poetry as a technical challenge. In the same way, the translations made in the 20th century seek to emphasize the sound aspects and the procedures used in the originals to constitute new, totally contemporary works.